Watkins Family Gathering at Home - Watkins, Howard::::::::: (1988)
Adam Watkins, Howard's Aunt Batsheva Eitan, Robin Watkins, Albert Watkins, his girlfriend Rose O'Reilly, Howard Watkins, Frances Kamp, and Christine Watkins seated by the round dining table Albert Watkins and Rose O'Reilly recently returned from a trip to Australia.